A rare non‐trilobite artiopodan from the Guzhangian (Cambrian Series 3) Weeks Formation Konservat‐Lagerstätte in Utah, USA. (24th October 2014) - Ortega‐Hernández, Javier; Lerosey‐Aubril, Rudy; Kier, Carlo; Bonino, Enrico; Zhang, Xi‐Guang
Abstract We describe a weakly biomineralized non‐trilobite artiopodan arthropod from the Guzhangian Weeks Formation of Utah. Falcatamacaris bellua gen. et sp. nov. is typified by a thin calcitic cuticle, broad cephalon without eyes or dorsal ecdysial sutures, an elongate trunk with distinctively sickle‐shaped pleural spines and a long tailspine with a bifurcate termination. The precise affinities of Falcatamacaris gen. nov. are problematic due to the presence of unique features within Artiopoda, such as the peculiar morphology of the pleural and posterior regions of the trunk. Possible affinities with aglaspidid‐like arthropods and concilitergans are discussed based on the possession of 11 trunk tergites, edge‐to‐edge articulations and overall body spinosity. The new taxon highlights the importance of the Weeks Formation Konservat‐Lagerstätte for further understanding the diversity of extinct arthropod groups in the upper Cambrian.